Cover Feature: Reconsidering Water Electrolysis: Producing Hydrogen at Cathodes Together with Selective Oxidation of n‐Butylamine at Anodes (ChemSusChem 24/2017). Issue 24 (13th December 2017) - Xue, Song; Watzele, Sebastian; Čolić, Viktor; Brandl, Kurt; Garlyyev, Batyr; Bandarenka, Aliaksandr S.
Abstract : The Cover Feature shows a new approach for water electrolysis, by rethinking the reaction at the anode: n ‐butyronitrile from n ‐butylamine is selectively produced as an easily retrievable valuable product, instead of oxygen gas. We study industrially relevant oxygen evolution reaction catalysts, CoO x, NiFeO x, and NiO x . They all show lower anodic potentials in the presence of n ‐butylamonium sulfate, without poisoning the active sites of Pt electrocatalyst for the hydrogen evolution electrode side. The highest activities were observed for NiO x thin‐film electrodes. More information can be found in the Communication by Xue, Watzele, et al. onpage 4812 in Issue 24, 2017 (DOI:10.1002/cssc.201701802 ).